The Man and Resources Program - Furlong, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary The Man and Resources program, and in particular the experience of the Task Force on Energy, was an interesting example of the criticism which faces scientific and professional people today. Modern society is questioning many of our values. Other "disciplines" like ecologists, sociologists and grass roots politicians have demonstrated that they can and will delay or veto important developments. The program which probably cost in excess of one million dollars, raised more hopes than solutions. The academic and professional societies from the "hard disciplines" should recognize the problem and provide leadership to the "soft disciplines" and the politicians and the concerned citizens.